Business communication (Vikas, 2013)
It constitute the lifeline off every business. People in every business need to communicate among themselves as well as with the outside world. Good communications results from clear understanding and conscious efforts. Therefore, it has become an essential subject of professional study. Mastering business communication skill, verbal as well as non-verbal, is a must for all those who aspire to succeed in the world of busines. This book follows a reader friendly approach in covering the significant aspect of business communication, and will be highly useful for both beginners and practitioners alike